2014
DOI: 10.1002/bmc.3249
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro metabolism of aspirin eugenol ester in dog by liquid chromatography tandem mass spectrometry

Abstract: Aspirin eugenol ester (AEE) is a promising drug candidate for treatment of inflammation, pain and fever and prevention of cardiovascular diseases with fewer side effects than its precursor, aspirin. Investigation into its metabolic process in target animal species will help to illustrate its mechanism of action and to establish its residual mark compound to formulate its dosage. Six beagle dogs were orally given a dose of 20 mg kg(-1) of AEE and one dog was used to prepare blank liver microsomes. Their liver m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Aspirin inhibit PLT aggregation through blocking TXA 2 synthesis which is a potent inducer of PLT aggregation and causes vasoconstriction [ 36 – 37 ]. In our previous study, the metabolites of AEE in vivo and in vitro have been confirmed [ 16 ]. In total, five metabolites were detected, including salicylic acid, salicylic acid glucuronide, salicylic acid glycine, eugenol glucuronide and eugenol sulfate.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Aspirin inhibit PLT aggregation through blocking TXA 2 synthesis which is a potent inducer of PLT aggregation and causes vasoconstriction [ 36 – 37 ]. In our previous study, the metabolites of AEE in vivo and in vitro have been confirmed [ 16 ]. In total, five metabolites were detected, including salicylic acid, salicylic acid glucuronide, salicylic acid glycine, eugenol glucuronide and eugenol sulfate.…”
Section: Discussionmentioning
confidence: 77%
“…In the Ames test and the mouse bone marrow micronucleus assay, the AEE did not show any mutagenesis [ 15 ]. Metabolites of AEE in vivo and in vitro also have been confirmed by HPLC-MS/MS, which indicated that AEE was decomposed into salicylic acid and eugenol [ 16 ]. Moreover, the evaluation for its anti-inflammatory, analgesic and antipyretic effects through animal model showed that AEE possessed similarity effects with aspirin, but lasted for a longer time [ 17 – 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The metabolites of AEE had been confirmed in beagle dog and liver microsomes. AEE could be metabolized into aspirin and eugenol in vitro and in vivo , which could show their original activities and act synergistically [10]. AEE also reduced the side effects of its precursor such as the gastrointestinal damage of aspirin and irritation of eugenol [11].…”
Section: Introductionmentioning
confidence: 99%
“…The acute toxicity of AEE is less than that of ASA and eugenol, only 0.02 times the toxicity of ASA and 0.27 times the toxicity of eugenol in mice [ 17 ]. AEE could be metabolized into ASA and eugenol in vitro and in vivo [ 18 ], and had the effects of anti-inflammation, antipyretic, analgesia, and antioxidant [ 15 , 19 ]. In addition, the previous research indicated that AEE (50 mg · kg −1 and 160 mg · kg −1 ) could reduce the serum TC and TG in rats with standard diet [ 16 ].…”
Section: Introductionmentioning
confidence: 99%